Prevaccination epidemiology of herpes zoster in Denmark: Quantification of occurrence and risk factors. Issue 42 (9th October 2017) - Schmidt, Sigrun A.J.; Vestergaard, Mogens; Baggesen, Lisbeth M.; Pedersen, Lars; Schønheyder, Henrik C.; Sørensen, Henrik T.
Highlights: An algorithm to identify zoster in the Danish health registries was examined. Zoster was identified using routinely collected prescription and hospital records. Zoster was confirmed in 87% of persons receiving antivirals recommended for zoster. Rates increased from 2.15 to 9.45 per 1000 person-years between ages 40 and 90 years. Rates were higher in persons with immunosuppression and certain chronic diseases. Abstract: Background: Herpes zoster (HZ) is a vaccine-preventable disease caused by reactivation of the varicella-zoster virus. Unfortunately, formulation of recommendations on routine immunization is hampered by a lack of data on disease burden, since most countries do not record cases of HZ in the general population. We developed and validated an algorithm to identify HZ based on routinely collected registry data and used it to quantify HZ occurrence and risk factors in Denmark prior to marketing of the HZ vaccine. Methods: We included patients aged ≥40 years with a first-time systemic Acyclovir, Valacyclovir, or Famciclovir prescription or a hospital-based HZ diagnosis in the Danish nationwide health registries during 1997–2013. In a validation substudy (n = 176), we computed the proportion of persons with HZ among patients who redeemed antiviral prescriptions. In a cohort study, we computed age-specific rates of HZ (45, 297, 258 person-years). In a case-control study, we then computed odds ratios (ORs) for common chronic diseases and immunosuppressive factors among HZ cases (n = 189, 025) vs. matched population controls (n = 945, 111). Results: Medical record review confirmed HZ in 87% (95% confidence interval: 79–93%) of persons ≥40 years who dispensed antivirals at doses recommended for HZ. HZ rates increased from 2.15/1000 person-years in 40-year-olds to 9.45/1000 person-years in 95-year-olds. Rates were highest in women. HZ was diagnosed during hospitalization among 3.5%. As expected, persons with severe immunosuppressive conditions had the highest ORs of HZ (between 1.82 and 4.12), but various autoimmune diseases, asthma, chronic kidney disease, and inhaled glucocorticoids were also associated with increased ORs (between 1.06 and 1.64). Conclusion: This algorithm is a valid tool for identifying HZ in routine healthcare data. It shows that HZ is common in Denmark, especially in patients with certain chronic conditions. Prioritized vaccination of such high-risk patients might be an option in countries considering alternatives to universal vaccination.